Comparison of Body Mass Index and Fat Indices in Predicting the Severity of Nonalcoholic Fatty Liver Disease Among Children Who Are Overweight and Obese - Chao, Hsun-Chin; Lin, Hsin-Yeh (Frontiers in Pediatrics, 2021)
ABSTRACT Background: Information of the relationships between body mass parameters and severity of fatty liver is deficient in pediatric non-alcoholic fatty liver disease (NAFLD). Methods: The relationships between body mass parameters (waist circumference [WC], body mass index [BMI], and abdominal subcutaneous fat thickness [ASFT]) and severity of fatty liver were prospectively evaluated in pediatric patients with overweight or obese, suffering from NAFLD. Ultrasonography was performed to assess fatty liver and its severity on a three grade scale (low-grade fatty liver [LGFL], grade 1 or 2; high grade fatty liver [HGFL], grade 3). Results: A total of 110 subjects (55 LGFL and 55 HGFL) aged 6.2-17.9 years were included. The WC, BMI, and ASFT values were significantly higher in HGFL group compared to LGFL group (p = 0.00004, 0.01, and 0.04, respectively). WC had greatest power to predict HGFL under receiver operating characteristic curve analyses, and was positively correlated with severity of fatty liver in subjects aged 6- to 12-year old and 13- to 17-year old (p = 0.007, and 0.0039, respectively). ASFT showed positive correlation with severity of fatty liver in subjects aged 13- to 17-year old (p = 0.04). Conclusions: WC, BMI, and ASFT are predictive of severe NAFLD among children with overweight and obesity, particularly WC has most predictive accuracy. Among the parameters, WC and ASFT are predictive in specific age groups.